2009
DOI: 10.1007/s00468-009-0328-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of chilling on photosynthesis and antioxidant enzymes in Hevea brasiliensis Muell. Arg.

Abstract: The aim of the present study was to assess the tolerance of Hevea brasiliensis to chilling temperatures since rubber production has been extended to sub-optimal environments. PB260 clone was used to analyze the responses of leaves chilled at 10°C during 96 h, as well as their recovery at 28°C. Some key parameters were used to evaluate photosynthetic apparatus functioning, membrane damage (electrolyte leakage) and oxidative stress. A shortterm response versus a long-term one have been recorded, the time point o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 63 publications
1
22
0
3
Order By: Relevance
“…P max was significantly decreased by night chilling treatment at 10°C, which was returned to 45-85% of pretreatment levels after a 3-day recovery (Table 1S). Our results were consistent with a previously reported study by Mai et al (2009), in which rubber trees were showed to withstand 4 days of chilling at 10°C and 50% of its photosynthetic ability was recovered after 3 days at 28°C. We suggest that night chilling at 10°C for several days does not cause any irreversible damage in the photosynthetic system of rubber trees; however, night chilling at 0-5°C in combination with subsequent full irradiance can cause evident photodamage in rubber trees.…”
Section: Discussionsupporting
confidence: 95%
See 1 more Smart Citation
“…P max was significantly decreased by night chilling treatment at 10°C, which was returned to 45-85% of pretreatment levels after a 3-day recovery (Table 1S). Our results were consistent with a previously reported study by Mai et al (2009), in which rubber trees were showed to withstand 4 days of chilling at 10°C and 50% of its photosynthetic ability was recovered after 3 days at 28°C. We suggest that night chilling at 10°C for several days does not cause any irreversible damage in the photosynthetic system of rubber trees; however, night chilling at 0-5°C in combination with subsequent full irradiance can cause evident photodamage in rubber trees.…”
Section: Discussionsupporting
confidence: 95%
“…More than half of the soluble proteins are important components of the photosynthetic apparatus and photodamage repair process (Pell et al 1994, Asada 2006, Danon 2012, and soluble proteins also play an important role in osmotic adjustment (He et al 2013). MDA, which is the product of membrane lipid peroxidation, was significantly increased after night chilling treatments at 5°C and 0°C, indicating that night chilling might induce the accumulation of ROS, and impair cell membranes of the photosynthetic system (Thomashow 1999, Mai et al 2009, Lei et al 2014. MDA and ROS can suppress the activities of photosynthetic enzymes such as ribulose-1,5-bisphosphate carboxylase/oxygenase.…”
Section: Discussionmentioning
confidence: 95%
“…RNA was isolated using CTAB extraction buffer as described by Chang et al (1993) and stored at −80 • C. First strand cDNAs were synthesized by reverse transcription using 2 g of total RNA in a final reaction volume of 20 l using the Super Script TM III first strand synthesis system for RT-PCR (Invitrogen, Paisley, UK) according to the manufacturer's instructions. PCR amplifications were performed as described by Mai et al (2009) using the primers indicated in Table 1. The PCR products were ligated into PGEM-Teasy vector (Promega, Charbonnières, France) and transformed into DH5␣ Escherichia coli strain, and the sequences were checked.…”
Section: Rna Isolation and Cdna Synthesismentioning
confidence: 99%
“…The real-time RT-PCR amplifications were done according to Mai et al 34 with the specific primers reported in Table 1. The oligonucleotides primers were constructed based on specific Populus EST database [http://genome.jgi-psf.org] the EST detected with the BLAST program.…”
Section: Methodsmentioning
confidence: 99%